Airborne Ns (NO2 and NH3) in the Rijeka Bay Area (Croatia), 1980–1995 - Ana Alebic-Juretic (The Scientific World Journal)
The determination of ambient levels of nitrogen dioxide (NO2) and ammonia (NH3) in the Rijeka Bay area started in 1980, as a part of the air quality monitoring programme. The results of 15 years of surveying (1980/81–1994/95) on ambient levels of these pollutants at two sampling sites are given in this work. Site 1 is located in the city, opposite the old petroleum refinery facilities, while Site 2 is located in the settlement 25 km from the city, opposite the eastern industrial zone. Annual means of NO2 varied between 34 and 60 μg/m3 at Site 1 and between 14 and 26 μg/m3 at Site 2, but do not follow the 40% reduction in industrial emissions of this pollutant, probably due to the dominant impact of other minor sources, like traffic. Yearly averages of NH3 were in the range of 13 to 26 μg/m3 at Site 1 and 7 to 16 μg/m3 at Site 2, and are practically constant during the period studied.